A cold-heat cycle resistant aerogel thermal insulation coating for industrial heat pipes and a preparation method thereof
Patent Information
- Application Number
- CN202611373148.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
上述方式主要改变涂层在常温状态下的静态承载能力,难以同时调节涂层的整体热变形、局部载荷传递及裂纹延伸路径
(1)本发明提供了一种工业热力管道用耐冷热循环气凝胶隔热涂料的制备方法,按照热膨胀调节粉体、耐高温无机粉体、片状矿物填料、空心颗粒及疏水二氧化硅气凝胶的粒径、形貌和结构强度差异实施分阶段顺序加料,使细粒粉体先在连续液相中充分润湿和分散,片状矿物填料随后形成交错阻隔结构,从而兼顾热变形调节、裂纹偏转和热传导路径延长,与该加料顺序相配合的分段降速混合,使前期高剪切作用满足致密粉体的解聚需要,并在片状填料、空心颗粒及气凝胶加入时逐步降低剪切强度,有利于促进前述组分在连续相中的均匀分布,降低冷热循环引起的界面应力集中及裂纹扩展,并提高涂层的隔热稳定性和服役耐久性。
Smart Images

Figure CN122878799A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial thermal insulation coating technology, and in particular to a cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines and its preparation method. Background Technology
[0002] Industrial thermal pipelines repeatedly experience heating and cooling during startup, shutdown, load adjustment, and intermittent operation. The pipe's metal substrate, the organic or inorganic binder phase, aerogel particles, and inorganic fillers in the insulation coating exhibit different thermal expansion characteristics. When the insulation coating adheres to the outer surface of the pipeline, the coating's free deformation is constrained by the metal pipeline. During repeated heating and cooling processes, periodic tensile stress, compressive stress, and interfacial shear stress are generated within the coating and between the coating and the metal pipeline.
[0003] Existing aerogel thermal insulation coatings typically disperse silica aerogel and hollow microspheres within the film-forming material. Hydrophobic silica aerogel possesses a porous framework, while hollow microspheres have a thin-walled hollow structure; both can reduce continuous solid-state heat transfer pathways within the coating. However, the porous framework and thin-walled hollow structure are highly sensitive to localized loads and shear forces. During coating preparation, when aerogel, hollow particles, and ordinary inorganic powders are dispersed at high speeds for extended periods, aerogel aggregates are prone to compaction or breakage, and the shells of hollow particles are susceptible to rupture, reducing the actual number of porous structures retained in the coating.
[0004] Furthermore, during repeated heating and cooling of the coating, the differences in thermal deformation between aerogel particles, hollow particles, inorganic fillers, and the continuous film-forming phase cause periodic stress to concentrate in the interfacial regions of different materials. With increasing thermal cycling cycles, localized stress can lead to aerogel skeleton damage, hollow particle shell cracking, and material interface debonding, subsequently forming microcracks. These microcracks, after continuously propagating along the coating thickness direction or along the coating-pipe interface, easily develop into through-cracks, localized blistering, and delamination.
[0005] In existing technologies, to improve the structural strength of aerogel thermal insulation coatings, the amount of binder is typically increased, or ordinary fibers and dense inorganic fillers are added. Increasing the amount of binder increases the proportion of continuous solid phase in the coating; adding more dense fillers alters the spatial distribution of aerogel and hollow particles. These methods primarily change the static load-bearing capacity of the coating at room temperature, making it difficult to simultaneously adjust the overall thermal deformation, local load transfer, and crack propagation path of the coating.
[0006] Therefore, the key technical problem of existing aerogel thermal insulation coatings for industrial thermal pipelines is that the thermal deformation between different materials within the coating and between the coating and the pipeline is not coordinated, resulting in periodic stress concentration during thermal cycling. This periodic stress further causes damage to the porous particle structure, debonding of the material interface, and microcrack propagation. At the same time, the high-speed mixing in conventional preparation processes can also pre-damage the aerogel and hollow particles, making it difficult for the coating to maintain both the porous thermal insulation structure and structural stability under thermal cycling conditions. Summary of the Invention
[0007] This invention overcomes the shortcomings of the prior art and provides a cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines and its preparation method.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines, comprising the following steps: S1. A water-based heat-resistant binder, water, dispersant, wetting agent, and first defoamer are mixed to obtain a continuous liquid phase; thermal expansion regulating powder and high-temperature resistant inorganic powder are added sequentially to the continuous liquid phase and dispersed to obtain a first slurry; the thermal expansion regulating powder contains one or more of zirconium tungstate, hafnium tungstate, zirconium molybdate, β-lithium nepheline, and cordierite; the high-temperature resistant inorganic powder contains one or more of rutile titanium dioxide, silicon carbide, iron oxide black, and zircon powder. S2. Reduce the mixing speed of the first slurry, add flaky mineral filler to the first slurry, mix, add thickener, and continue mixing to obtain the second slurry; the flaky mineral filler includes one or more of sericite, mica powder, expanded vermiculite, flaky talc, and flaky kaolin. S3. Reduce the mixing speed of the second slurry, add hollow particles to the second slurry in batches, mix, add hydrophobic silica aerogel, and continue mixing to obtain the third slurry; the hollow particles include one or more of hollow glass microspheres, hollow ceramic microspheres, and cenospheres; S4. Add anti-settling agent, leveling agent and second defoamer to the third slurry, mix and adjust to the target viscosity with water, and defoam to obtain the cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines. In step S1, the dispersion speed is greater than the mixing speed in step S2, and in step S2, the mixing speed is greater than the mixing speed after adding hydrophobic silica aerogel in step S3.
[0009] In a preferred embodiment of the present invention, the preparation of the continuous liquid phase in step S1 includes: Mix 20-40 parts by weight of water-based heat-resistant adhesive, 8-25 parts by weight of water, 0.2-1.5 parts by weight of dispersant, 0.1-0.8 parts by weight of wetting agent and 0.05-0.5 parts by weight of first defoamer; The waterborne heat-resistant adhesive comprises one or more of waterborne organosilicon resin, waterborne silicone-acrylic emulsion, waterborne siloxane resin, waterborne silicate adhesive, and waterborne organic-inorganic hybrid resin, wherein the solid content of the waterborne heat-resistant adhesive is 35% to 65%. The dispersant comprises one or more of polycarboxylate dispersants, polyacrylate dispersants, polyphosphate dispersants, and nonionic polymeric dispersants. The wetting agent comprises one or more of polyether-modified siloxane wetting agents, acetylsalicylic acid diol wetting agents, and nonionic polyether wetting agents. The mixing speed of the continuous liquid phase is 300-900 r / min, the mixing time is 5-20 min, and the mixing temperature is 15-40℃.
[0010] In a preferred embodiment of the present invention, the addition and dispersion of the thermal expansion regulating powder in step S1 includes: Add 4 to 20 parts of the thermal expansion regulating powder to the continuous liquid phase according to the mass fraction; The thermal expansion regulating powder contains at least one of zirconium tungstate, hafnium tungstate, and zirconium molybdate, and at least one of β-nepheline and cordierite; The ratio of the total mass of zirconium tungstate, hafnium tungstate, and zirconium molybdate to the total mass of β-lithium nepheline and cordierite is 1:0.3 to 1:4. Furthermore, when the thermal expansion regulating powder is composed of zirconium tungstate and β-lithium nepheline, the mass ratio of zirconium tungstate to β-lithium nepheline is preferably 1:0.6 to 1:1.7. The D50 of the zirconium tungstate, hafnium tungstate, and zirconium molybdate is 0.2–8 μm, and the D50 of the β-lithium nepheline and cordierite is 1–20 μm. The thermal expansion regulating powder is added in 2 to 5 batches, with a time interval of 1 to 8 minutes between adjacent batches. After each batch is added, it is dispersed at 900 to 2200 r / min for 3 to 12 minutes. After all the powder is added, it is dispersed at 1000 to 2500 r / min for 10 to 35 minutes.
[0011] In a preferred embodiment of the present invention, the addition and dispersion of the high-temperature resistant inorganic powder in step S1 includes: According to the mass fraction, add 2 to 15 parts of the high-temperature resistant inorganic powder to the continuous liquid phase after adding the thermal expansion regulating powder; The high-temperature resistant inorganic powder includes a first inorganic powder and a second inorganic powder. The first inorganic powder contains at least one of rutile titanium dioxide and zircon powder, and the second inorganic powder contains at least one of silicon carbide and iron oxide black. The mass ratio of the first inorganic powder to the second inorganic powder is 1:0.1 to 1:2; The rutile titanium dioxide has a D50 of 0.1–1.5 μm, and the silicon carbide, iron oxide black, and zircon powder have D50s of 0.5–15 μm, respectively. The high-temperature resistant inorganic powder is added at a feeding rate of 0.2 to 2.0 kg / min, and the dispersion speed during the feeding process is 1000 to 2500 r / min. After the feeding is completed, the dispersion continues for 10 to 40 min to obtain a first slurry with a fineness of 20 to 80 μm.
[0012] In a preferred embodiment of the present invention, the addition and mixing of the flaky mineral filler in step S2 includes: According to the mass fraction, add 4 to 18 parts of the flaky mineral filler to the first slurry; The flaky mineral filler comprises sericite or mica powder, and contains at least one of expanded vermiculite, flaky talc, and flaky kaolin. The ratio of the total mass of the sericite and mica powder to the total mass of the expanded vermiculite, flaky talc, and flaky kaolin is 1:0.2 to 1:3. The D50 of the sheet-like mineral filler is 10-100 μm, and the aspect ratio is 10:1-80:1. The flaky mineral filler is added in 3 to 6 batches, with each batch containing 10% to 40% of the total mass of the flaky mineral filler. The mixing speed during the feeding process is 300 to 800 r / min, and each batch is mixed for 3 to 10 minutes after addition. After all the flaky mineral filler is added, 0.1 to 1.5 parts by weight of thickener is added, and the mixture is stirred at 200 to 700 r / min for 10 to 30 min to obtain the second slurry.
[0013] In a preferred embodiment of the present invention, the addition and mixing of hollow particles in step S3 includes: Add 8 to 28 parts of the hollow particles to the second slurry according to the mass fraction; The hollow particles comprise at least one of hollow glass microspheres and hollow ceramic microspheres, and also include cenospheres; The ratio of the total mass of the hollow glass microspheres and hollow ceramic microspheres to the mass of the cenospheres is 1:0.1 to 1:2; The hollow glass microspheres have a particle size of 15–120 μm, the hollow ceramic microspheres have a particle size of 20–150 μm, and the cenospheres have a particle size of 30–180 μm. The bulk density of the hollow particles is 0.08–0.65 g / cm³. 3 ; The hollow particles are added in 4 to 8 batches, with each batch accounting for 8% to 30% of the total mass of the hollow particles. The mixing speed during the feeding process is 100 to 500 r / min. After each batch is added, the mixture is mixed for 2 to 8 minutes. After all the hollow particles have been added, the mixture continues to be mixed for 5 to 20 minutes.
[0014] In a preferred embodiment of the present invention, the addition and mixing of hydrophobic silica aerogel in step S3 includes: According to the mass fraction, after all the hollow particles have been added, 5 to 22 parts of hydrophobic silica aerogel are added to the second slurry. The hydrophobic silica aerogel is one or both of granular hydrophobic silica aerogel and powdered hydrophobic silica aerogel. The hydrophobic silica aerogel has a particle size of 5–100 μm and a bulk density of 0.03–0.20 g / cm³. 3 The pore size is 10–100 nm; The surface of the hydrophobic silica aerogel contains one or more of trimethylsiloxy, dimethylsiloxy and methylsiloxy groups; Before adding the hydrophobic silica aerogel, the mixing speed in step S3 is adjusted to 50-250 r / min; The hydrophobic silica aerogel is added continuously at a feeding rate of 0.05–0.8 kg / min or in 2–6 batches. After the feeding is completed, it is mixed at 80–250 r / min for 5–20 min at a mixing temperature of 15–35 °C to obtain the third slurry.
[0015] In a preferred embodiment of the present invention, step S4 includes: According to the mass fractions, add 0.1 to 1.5 parts of anti-settling agent, 0.05 to 0.8 parts of leveling agent and 0.05 to 0.6 parts of second defoamer to the third slurry; The anti-settling agent comprises one or more of water-based bentonite, modified attapulgite, polyamide wax, and fumed silica. The leveling agent comprises one or both of polyether-modified siloxane leveling agents and polyacrylate leveling agents; The mass ratio of the first defoamer to the second defoamer is 1:0.3 to 1:3; After adding the anti-settling agent, leveling agent, and second defoamer, mix at 100–500 r / min for 8–30 min, and add 0.5–8 parts by weight of water to adjust the viscosity of the coating at 25°C to 5 × 10⁻⁶. 3 ~4×10 4 mPa·s; After viscosity adjustment, degas for 5–30 minutes at 15–40℃ and 10–70 kPa absolute pressure.
[0016] In a preferred embodiment of the present invention, step S3 employs a segmented deceleration mixing method, including: Before adding the hollow particles, the second slurry is mixed at 300-600 r / min for 2-8 min; During the addition of the hollow particles, the mixing speed is adjusted to 150–450 r / min; After the hollow particles are added, adjust the mixing speed to 100-350 r / min and mix for 5-15 min. Before adding the hydrophobic silica aerogel, the mixing speed is adjusted to 50-200 r / min; During the addition of the hydrophobic silica aerogel, the mixing speed is maintained at 80–120 r / min; After the hydrophobic silica aerogel is added, the mixing speed is adjusted to 80-250 r / min, and the mixture is mixed for 5-20 min. The total mixing time in step S3 is 20 to 70 minutes, and the time interval between the completion of adding the hollow particles and the start of adding the hydrophobic silica aerogel is 1 to 10 minutes.
[0017] This invention also provides a cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines, comprising, by weight parts: 20-40 parts of water-based heat-resistant adhesive; Water 8.5–33 parts; Dispersant 0.2–1.5 parts; Wetting agent 0.1 to 0.8 parts; Defoamer 0.1 to 1.1 parts; 4-20 parts of thermal expansion regulating powder; 2-15 parts of high-temperature resistant inorganic powder; 4-18 parts of flaky mineral filler; Thickener 0.1 to 1.5 parts; Hollow granules, 8-28 parts; 5–22 parts of hydrophobic silica aerogel; Anti-settling agent 0.1–1.5 parts; Leveling agent 0.05–0.8 parts; The thermal expansion regulating powder contains at least one of zirconium tungstate, hafnium tungstate, and zirconium molybdate, and at least one of β-nepheline and cordierite; The high-temperature resistant inorganic powder includes a first inorganic powder and a second inorganic powder. The first inorganic powder contains at least one of rutile titanium dioxide and zircon powder, and the second inorganic powder contains at least one of silicon carbide and iron oxide black. The flaky mineral filler comprises sericite or mica powder, and contains at least one of expanded vermiculite, flaky talc, and flaky kaolin. The hollow particles comprise at least one of hollow glass microspheres and hollow ceramic microspheres, and also include cenospheres; The hydrophobic silica aerogel has a particle size of 5–100 μm, the hollow particles have a particle size of 15–180 μm, and the sheet-like mineral filler has a D50 of 10–100 μm and a diameter-to-thickness ratio of 10:1–80:1.
[0018] This invention addresses the shortcomings of the prior art and has the following beneficial effects: (1) This invention provides a method for preparing a thermally resistant aerogel thermal insulation coating for industrial thermal pipelines. The method involves adding materials in stages according to the differences in particle size, morphology and structural strength of thermal expansion regulating powder, high temperature resistant inorganic powder, flake mineral filler, hollow particles and hydrophobic silica aerogel. This allows the fine powder to be fully wetted and dispersed in the continuous liquid phase first, and the flake mineral filler to form an interlaced barrier structure. This achieves both thermal deformation regulation, crack deflection and extension of the heat conduction path. The staged slow-down mixing, which is coordinated with the feeding sequence, ensures that the high shear force in the early stage meets the deagglomeration requirements of the dense powder. The shear strength is gradually reduced when the flake filler, hollow particles and aerogel are added, which is beneficial to promote the uniform distribution of the aforementioned components in the continuous phase, reduce the interface stress concentration and crack propagation caused by thermal cycling, and improve the thermal insulation stability and service durability of the coating.
[0019] In this invention, zirconium tungstate, through its thermal expansion regulation characteristics, compensates for the overall thermal deformation of the continuous film-forming phase and the inorganic filler system, making the overall dimensional changes of the coating during thermal cycling closer to those of the metal substrate, thereby reducing the periodic thermal stress caused by interfacial thermal mismatch. β-Lithium nepheline has low thermal expansion characteristics, and its dispersion in the continuous film-forming phase further mitigates the local thermal deformation gradient between different components, promotes the uniform transmission of the thermal expansion compensation effect of zirconium tungstate throughout the coating, reduces stress concentration near the particle interface, and ensures that the overall thermal deformation of the coating maintains a high degree of matching with the substrate. At the same time, it reduces the initiation and propagation of microcracks during thermal cycling, and improves the thermal cycling stability and thermal insulation structural integrity of the coating.
[0020] In this invention, hydrophobic silica aerogel is added to the slurry at a suitable mixing speed. This ensures that the particles are fully wetted and uniformly dispersed, while reducing structural damage to the nanoporous framework caused by fluid shearing and particle collisions. This maintains the porous network and low thermal conductivity of the aerogel. Hollow particles, after being pre-dispersed stably, form a relatively uniform spatial framework, providing a stable dispersion environment for subsequent aerogel particles. This reduces the probability of local aggregation and collisions between aerogel particles and between aerogel and hollow particles, further promoting the maintenance of the porous structure of the aerogel. This allows the porous thermal insulation structure of the aerogel and the hollow thermal insulation structure of the hollow particles to form a continuous composite thermal insulation system. At the same time, it maintains a uniform pore distribution and a stable load transfer path, thereby improving the thermal insulation performance of the coating and its structural stability under thermal cycling conditions. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Figure 1 This is a flowchart illustrating the method steps of a preferred embodiment of the present invention. Detailed Implementation
[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0024] Application Overview: The thermal insulation coating on the outer surface of industrial thermal pipelines is typically directly constrained by the deformation of the metal pipeline. When the pipeline heats up, both the pipeline substrate and the coating undergo thermal expansion; when the pipeline cools down, both the pipeline substrate and the coating shrink. Due to the different thermal deformation characteristics of the continuous film phase, aerogel, hollow particles, and dense inorganic fillers, the phases cannot maintain completely uniform dimensional changes, thus creating repeatedly varying stresses within the coating and at the interface between the coating and the pipeline.
[0025] This invention incorporates thermal expansion regulating powder, hollow particles, and flake-shaped mineral fillers into the coating. The thermal expansion regulating powder participates in regulating the overall thermal deformation of the coating; the hollow particles form dispersed hollow structural regions, altering the direct transmission path of concentrated loads; and the flake-shaped mineral fillers, distributed in an alternating pattern, block and deflect crack propagation. These three types of materials correspond to the three stages of overall dimensional change, local load transmission, and crack propagation, respectively.
[0026] Furthermore, the present invention sets the feeding sequence according to the particle size, morphology, and shear resistance. Fine-grained thermal expansion regulating powder and high-temperature resistant inorganic powder are first wetted and dispersed in a continuous liquid phase; the flake-shaped mineral filler is added after the rotation speed is reduced; hollow particles are added in batches at an even lower rotation speed; and hydrophobic silica aerogel is added in the final stage. This preparation sequence allows the aerogel and hollow particles to bypass the high-speed dispersion stage of step S1 and reduces the time the flake-shaped mineral filler undergoes high-shear mixing.
[0027] Thus, the resulting coating is composed of a continuous film-forming phase, porous aerogel particles, hollow particles, plate-like mineral fillers, and fine-grained inorganic powders. The continuous film-forming phase connects various particles and adheres to the pipe surface. The hydrophobic silica aerogel and hollow particles form porous regions of different sizes. The thermal expansion regulating powder and plate-like mineral fillers are distributed between the porous regions and the continuous film-forming phase.
[0028] The industrial thermal pipelines of this invention include metal pipelines for transporting steam, hot water, heat transfer oil, high-temperature flue gas heat tracing media, high-temperature petrochemical materials, and industrial waste heat media.
[0029] Specifically, the metal pipe can be a carbon steel pipe, stainless steel pipe, low alloy steel pipe, cast steel pipe, or cast iron pipe. The coating can be applied to straight pipe sections, elbows, tees, reducers, valves, flanges, pipe support adjacent areas, and other irregular connection parts.
[0030] In one embodiment, the coating is applied to the outer surface of a Q235 steel pipe that has undergone degreasing and rust removal treatment. The outer diameter of the steel pipe is 50–500 mm, and the dry film thickness of the coating is 1–10 mm. The coating can be applied by brushing, rolling, air spraying, airless spraying, or scraping.
[0031] Furthermore, when a single coat cannot achieve the designed thickness, a layered application method can be used. Each wet film layer can be 0.5–3.0 mm thick, with the next layer applied after the previous one has reached a surface-dry state. Each layer of coating can use the same formula, or the amounts of binder, hollow particles, and aerogel in the top and bottom layers can be adjusted.
[0032] In this invention, an aqueous heat-resistant binder is used to form a continuous film-forming phase and to connect hydrophobic silica aerogel, hollow particles, and inorganic fillers after the coating has cured; a dispersant is used to promote the wetting and dispersion of thermal expansion regulating powder and high-temperature resistant inorganic powder in the continuous liquid phase; and a wetting agent is used to improve the wettability between the inorganic powder and the continuous liquid phase.
[0033] The waterborne heat-resistant adhesive used is DOWSIL™ 8016 Waterborne Resin manufactured by Dow Chemical Company, USA. This material is an organosilicon resin emulsion for waterborne high-temperature coating systems, and can be used for the protection of metal substrates and the formulation of high-temperature coatings containing pigments and fillers.
[0034] The hollow glass microspheres used are 3M™ K37 hollow glass microspheres manufactured by 3M, with a standard median particle size of 45 μm and a true density of 0.37 g / cm³. 3 It is composed of sodium calcium borosilicate glass, and its official applications include paints and coatings, anti-sagging thick film coatings, and high-temperature heat insulation coatings.
[0035] Hydrophobic silica aerogels are made from dried silica aerogel particles or powders with a particle size of 5–100 μm and a bulk density of 0.03–0.20 g / cm³. 3 The pore size is 10–100 nm.
[0036] Specifically, the surface of the hydrophobic silica aerogel contains trimethylsiloxy, dimethylsiloxy, or methylsiloxy groups. Before use, the aerogel is dried at 80°C for 2 hours and then cooled to room temperature in a sealed container.
[0037] Hydrophobic fumed silica and hydrophobic silica aerogel are different materials. Hydrophobic fumed silica is mainly used as a rheology modifier or anti-settling agent, while hydrophobic silica aerogel has a three-dimensional porous framework and serves as a major thermal insulation component. In this invention, the two cannot be considered the same raw material simply because they both contain SiO2 in their chemical composition.
[0038] In one embodiment, the anti-settling agent is AEROSIL® R972V hydrophobic fumed silica from Evonik. This product is surface-treated with dimethyldichlorosilane and is listed as a hydrophobic fumed silica suitable for coatings.
[0039] Zirconium tungstate has the chemical formula ZrW₂O₈, a purity of not less than 98%, and a D₅₀ of 0.5–5 μm. Hafnium tungstate has the chemical formula HfW₂O₈, a purity of not less than 98%, and a D₅₀ of 0.5–5 μm. Zirconium molybdate has the chemical formula ZrMo₂O₈, a purity of not less than 98%, and a D₅₀ of 0.5–8 μm.
[0040] β-Legnum nepheline powder has LiAlSiO4 as the main crystalline phase, with a D50 of 2–15 μm. Cordierite powder has Mg2Al4Si5O4 as the main crystalline phase. 18 It is the main crystalline phase, with a D50 of 3–20 μm.
[0041] In a preferred embodiment, zirconium tungstate and β-lithium nepheline together form a thermal expansion regulating powder, and the mass ratio of zirconium tungstate to β-lithium nepheline is 1:0.6 to 1:1.7.
[0042] Rutile titanium dioxide has a TiO2 content of no less than 92% and a D50 of 0.2–0.5 μm. Silicon carbide uses green or black silicon carbide micropowder with a SiC content of no less than 97% and a D50 of 1–10 μm. Iron oxide black has Fe3O4 as its main component and a D50 of 0.5–5 μm. Zircon powder has ZrSiO4 as its main component and a D50 of 1–10 μm.
[0043] The high-temperature resistant inorganic powder includes a first inorganic powder and a second inorganic powder. The first inorganic powder contains at least one of rutile titanium dioxide and zircon powder, and the second inorganic powder contains at least one of silicon carbide and iron oxide black. The mass ratio of the first inorganic powder to the second inorganic powder is 1:0.1 to 1:2.
[0044] In one specific embodiment, the first inorganic powder is rutile titanium dioxide, and the second inorganic powder is silicon carbide, with a mass ratio of rutile titanium dioxide to silicon carbide of 1:0.1 to 1:1. In other embodiments, the first inorganic powder may also be zircon powder, and the second inorganic powder may also be iron oxide black.
[0045] The D50 of sericite and mica powder is 15–60 μm, with an aspect ratio of 20:1–80:1. The D50 of expanded vermiculite is 30–100 μm, with an aspect ratio of 10:1–40:1. The D50 of flaky talc and flaky kaolinite is 10–50 μm, with an aspect ratio of 10:1–50:1.
[0046] Before use, the flaky mineral packing material can be dried at 105℃ for 2 hours to remove adsorbed water. After drying, the flaky mineral packing material should be sieved through a 100-300 mesh sieve and stored in a sealed container.
[0047] The dispersant is a polycarboxylate dispersant or polyacrylate dispersant suitable for water-based coatings, with a solid content of 30%–50%. The wetting agent is a polyether-modified siloxane wetting agent or an acetylenic diol wetting agent. The defoamer is a mineral oil defoamer, a polyether defoamer, or an organosilicon defoamer.
[0048] The thickener is a nonionic polyurethane associative thickener, a cellulose ether thickener, or an acrylic associative thickener. The leveling agent is a polyether-modified siloxane leveling agent or a polyacrylate leveling agent.
[0049] like Figure 1 As shown, a method for preparing a cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines includes the following steps: S1. A water-based heat-resistant binder, water, dispersant, wetting agent, and first defoamer are mixed to obtain a continuous liquid phase; thermal expansion regulating powder and high-temperature resistant inorganic powder are added sequentially to the continuous liquid phase and dispersed to obtain a first slurry; the thermal expansion regulating powder includes one or more of zirconium tungstate, hafnium tungstate, zirconium molybdate, β-lithium nepheline, and cordierite; the high-temperature resistant inorganic powder includes one or more of rutile titanium dioxide, silicon carbide, iron oxide black, and zircon powder; S2. Reduce the mixing speed of the first slurry, add flaky mineral filler to the first slurry, mix, add thickener, and continue mixing to obtain the second slurry; the flaky mineral filler includes one or more of sericite, mica powder, expanded vermiculite, flaky talc, and flaky kaolin. S3. Reduce the mixing speed of the second slurry, add hollow particles to the second slurry in batches, mix, add hydrophobic silica aerogel, and continue mixing to obtain the third slurry; the hollow particles include one or more of hollow glass microspheres, hollow ceramic microspheres, and cenospheres; S4. Add anti-settling agent, leveling agent and second defoamer to the third slurry, mix and adjust to the target viscosity with water, and defoam to obtain aerogel heat insulation coating for industrial thermal pipelines that is resistant to cold and heat cycles. In step S1, the dispersion speed is greater than the mixing speed in step S2, and in step S2, the mixing speed is greater than the mixing speed after adding hydrophobic silica aerogel in step S3.
[0050] In step S1: Add water-based heat-resistant adhesive, water, dispersant, wetting agent and first defoamer to the mixing system and mix at 300-900 r / min for 5-20 min to form a continuous liquid phase.
[0051] In this invention, the continuous liquid phase refers to a liquid system formed by an aqueous heat-resistant binder, water, and liquid additives before the addition of the main inorganic particles. After the coating cures, the continuous liquid phase forms a continuous film-forming phase connecting the aerogel, hollow particles, and inorganic fillers.
[0052] More specifically, first add the water-based heat-resistant binder and water accounting for 60% to 90% of the total water in the formula, and mix at 300 to 600 r / min for 3 to 10 min; then add the dispersant, wetting agent and first defoamer, and increase the speed to 500 to 900 r / min, and continue mixing for 5 to 15 min.
[0053] Add the thermal expansion regulating powder to the continuous liquid phase in batches. The thermal expansion regulating powder is added in 2 to 5 batches, with an interval of 1 to 8 minutes between adjacent batches. After each batch is added, disperse at 900 to 2200 r / min for 3 to 12 minutes, and after all batches are added, continue to disperse at 1000 to 2500 r / min for 10 to 35 minutes.
[0054] Subsequently, high-temperature resistant inorganic powder was added at a feeding rate of 0.2–2.0 kg / min. During the feeding process, the dispersion speed was maintained at 1000–2500 r / min. After the feeding was completed, dispersion was continued for 10–40 min to obtain the first slurry.
[0055] The thermal expansion regulating powder and the high-temperature resistant inorganic powder in step S1 are both inorganic powders with small particle size and high particle strength. This step uses a high dispersion speed to ensure that the fine powder particles are wetted and de-agglomerated in the continuous liquid phase. The fineness of the first slurry is controlled to be 20–80 μm.
[0056] In step S2: Reduce the mixing speed of the first slurry to 300–800 r / min, and add the flaky mineral filler in batches. The flaky mineral filler is added in 3–6 batches, with each batch accounting for 10%–40% of the total mass of the flaky mineral filler. Mix each batch for 3–10 min.
[0057] After all the flaky mineral filler is added, a thickener is added, and the mixture is continued to be mixed at 200-700 r / min for 10-30 min to obtain the second slurry.
[0058] More specifically, when using cellulose ether thickeners, the cellulose ether and water can be premixed at a mass ratio of 1:10 to 1:30 before being added to the first slurry; when using polyurethane associative thickeners, the first slurry can be added directly and slowly.
[0059] The mixing speed in step S2 is lower than the dispersion speed in step S1. The flaky mineral packing is not subjected to the high-speed dispersion in step S1 to reduce the breakage of the flaky particles and the decrease in the aspect ratio.
[0060] In step S3: Before adding the hollow particles, mix the second slurry at 300–600 r / min for 2–8 min; then adjust the mixing speed to 150–450 r / min and add the hollow particles in 4–8 batches. The amount added in each batch is 8%–30% of the total mass of the hollow particles, and mix for 2–8 min after each batch.
[0061] After all the hollow particles are added, adjust the mixing speed to 100-350 r / min and continue mixing for 5-15 min; then reduce the mixing speed to 50-200 r / min and add the hydrophobic silica aerogel.
[0062] The hydrophobic silica aerogel can be added continuously at a rate of 0.05–0.8 kg / min, or in 2–6 batches. During the aerogel addition process, the mixing speed should be maintained at 80–120 r / min. After all the aerogel has been added, mix at 80–250 r / min for 5–20 min to obtain the third slurry.
[0063] It is important to emphasize that the hydrophobic silica aerogel should be added only after all the hollow particles have been added. The aerogel should not be dispersed at high speed together with the thermal expansion regulating powder and the high-temperature resistant inorganic powder, nor should it be added before the addition of the flaky mineral filler.
[0064] In step S4: Add anti-settling agent, leveling agent and second defoamer to the third slurry, and mix at 100-500 r / min for 8-30 min.
[0065] Then add the remaining water to adjust the viscosity of the coating at 25°C to 5×10³~4×10. 4 Viscosity can be measured using a rotational viscometer. During testing, the appropriate rotor and rotational speed should be selected based on the viscosity range.
[0066] After viscosity adjustment, degas for 5–30 minutes at 15–40℃ and 10–70 kPa absolute pressure. After degassing, filter through a 40–100 mesh sieve or fill directly to obtain a cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines.
[0067] Unless otherwise specified, the waterborne heat-resistant adhesive used in the following examples is DOWSIL™ 8016 Waterborne Resin waterborne silicone resin emulsion manufactured by Dow Chemical, with a solid content of 50.0%; the dispersant is BYK DISPERBYK-190 waterborne wetting and dispersing agent with a solid content of 40.0%; the wetting agent is BYK-348 waterborne silicone surfactant from BYK; both the first and second defoamers are BYK-024 waterborne silicone defoamer from BYK; the thickener is BYK RHEOBYK-M 2600 nonionic polyurethane associative thickener from BYK; the anti-settling agent is Evonik AEROSIL® R 972 V hydrophobic fumed silica; and the leveling agent is BYK-333 silicone surface additive from BYK. All the above additives were used directly without further purification.
[0068] The rutile titanium dioxide used is Chemours Ti-Pure™ R-706 coating-grade rutile titanium dioxide, with a D50 of 0.32 μm measured by a laser particle size analyzer; the silicon carbide used is Fiven SIKA® TECH series black silicon carbide micro powder, with a SiC content of not less than 97.0% and a D50 of 4.8 μm; the hollow glass microspheres used are 3M™ GlassBubbles K37 from 3M, with a standard median particle size of 45 μm and a typical true density of 0.37 g / cm³; the cenospheres used are ZUMiR Kazakhstan Premium Dry cenospheres, with a batch D50 of 82 μm and a bulk density of 0.38 g / cm³ after sieving.
[0069] Zirconia tungstate was produced by Shanghai Epoch Material Co., Ltd., using EP-ZrW2O8 type zirconium tungstate powder with a purity of not less than 99.5% and a particle size of 0.5–3.0 μm. The batch used had a D50 of 2.1 μm. β-Limonite was supplied by ChemicalCell as Eucryptite (AlLi(SiO4)) β-phase product, with specifications of β-phase, LiAlSiO4 content not less than 98.0%, and D50 of 1–10 μm. The batch used had a D50 of 8.6 μm, and X-ray diffraction confirmed that the main crystalline phase was β-LiAlSiO4. Sericite was produced by GOYEN CHEMICAL INDUSTRIAL CO., LTD., using GYM-400 type sericite powder with a batch D50 of 35 μm and an average aspect ratio of 45:1. Flaky kaolin was produced by 20 Microns Ltd., using Delam Clay 802. Type C flaked kaolin, the batch used had a D50 of 22 μm and an average diameter-to-thickness ratio of 26:1.
[0070] The hydrophobic silica aerogel used was Kramar 091458 hydrophobic silica aerogel powder purchased from Shanghai Koraman Reagent Co., Ltd. The tested D50 was 38 μm, the bulk density was 0.095 g / cm³, the average pore size was 28 nm, and the surface contained trimethylsiloxy groups. Before use, it was dried at 80℃ for 2 h and cooled to 23±2℃ in a sealed container.
[0071] Example 1: This example provides a cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines, the raw materials of which include: The composition includes 30 parts water-based heat-resistant binder, 18 parts water, 0.8 parts dispersant, 0.4 parts wetting agent, 0.2 parts primary defoamer, 5 parts zirconium tungstate, 3 parts β-lithium nepheline, 4 parts rutile titanium dioxide, 2 parts silicon carbide, 6 parts sericite, 3 parts flaky kaolin, 0.6 parts thickener, 12 parts hollow glass microspheres, 4 parts cenospheres, 12 parts hydrophobic silica aerogel, 0.5 parts anti-settling agent, 0.3 parts leveling agent, and 0.2 parts secondary defoamer.
[0072] The total amount of zirconium tungstate and β-lithium nepheline used was 8 parts.
[0073] The preparation method of this embodiment includes the following steps.
[0074] S1. Add 30 parts of water-based heat-resistant adhesive and 15 parts of water to the mixing system and mix at 400 r / min for 5 min; then add 0.8 parts of dispersant, 0.4 parts of wetting agent and 0.2 parts of first defoamer, increase the mixing speed to 700 r / min, and continue mixing for 10 min to obtain a continuous liquid phase.
[0075] Zirconium tungstate and β-lithium nepheline were mixed for 5 minutes to obtain 8 portions of thermal expansion regulating powder. The thermal expansion regulating powder was divided into 4 batches of 2 portions each.
[0076] Add the first batch of thermal expansion regulating powder to the continuous liquid phase and disperse at 1400 r / min for 5 min; add the remaining 3 batches of thermal expansion regulating powder in the same manner, with a 2 min interval between each batch. After all the thermal expansion regulating powder has been added, continue dispersing at 1800 r / min for 20 min.
[0077] Four parts of rutile titanium dioxide and two parts of silicon carbide were premixed and added to the aforementioned slurry at a feeding rate of 0.5 kg / min, while maintaining a dispersion speed of 1800 r / min during the feeding process. After the feeding was completed, dispersion was continued for 20 min to obtain the first slurry.
[0078] S2. Reduce the mixing speed of the first slurry to 600 r / min. Premix 6 parts sericite and 3 parts flaky kaolinite, and divide them into 3 equal batches of 3 parts each. After each batch of flaky mineral filler is added, mix at 600 r / min for 5 minutes.
[0079] After all the flaky mineral filler is added, 0.6 parts of thickener are added at 300 r / min, and then mixed at 450 r / min for 20 min to obtain the second slurry.
[0080] S3. Mix the second slurry at 450 r / min for 5 min, then reduce the speed to 300 r / min. After lightly mixing 12 parts of hollow glass microspheres and 4 parts of cenospheres, divide them into 4 equal batches of 4 parts each.
[0081] Four batches of hollow particles were added to the second slurry sequentially, and after each batch was added, the mixture was stirred at 300 r / min for 4 min. After all the hollow particles were added, the mixing speed was reduced to 220 r / min, and the mixture was stirred for another 10 min.
[0082] The mixing speed was then reduced to 80 rpm, and the 12 portions of hydrophobic silica aerogel were divided into 4 batches of 3 portions each. Each batch of hydrophobic silica aerogel was added over 2 minutes.
[0083] After all the hydrophobic silica aerogel was added, it was mixed at 160 r / min for 12 min to obtain the third slurry.
[0084] S4. Add 0.5 parts of anti-settling agent, 0.3 parts of leveling agent and 0.2 parts of second defoamer to the third slurry, and mix at 300 r / min for 15 min.
[0085] Add the remaining 3 parts water, mix at 250 r / min for 10 min, and adjust the viscosity of the coating at 25℃ to 18000~20000 mPa·s.
[0086] The obtained coating was defoamed for 15 minutes at 25℃ and 35kPa absolute pressure to obtain a cold and hot cycle resistant aerogel insulation coating for industrial thermal pipelines.
[0087] Example 2: The only difference between this example and Example 1 is the mass distribution of zirconium tungstate and β-lithium nepheline.
[0088] In this embodiment, the amount of zirconium tungstate is 4 parts, the amount of β-lithium nepheline is 4 parts, and the total amount of the two is still 8 parts.
[0089] Except for the amounts of zirconium tungstate and β-lithium nepheline, the types and amounts of other raw materials, the total amount of thermal expansion regulating powder, and all preparation processes are the same as in Example 1.
[0090] Example 3: The only difference between this example and Example 1 is the mass distribution of zirconium tungstate and β-lithium nepheline.
[0091] In this embodiment, the amount of zirconium tungstate is 3 parts, the amount of β-lithium nepheline is 5 parts, and the total amount of both is still 8 parts.
[0092] Except for the amounts of zirconium tungstate and β-lithium nepheline, the types and amounts of other raw materials, the total amount of thermal expansion regulating powder, and all preparation processes are the same as in Example 1.
[0093] Example 4: The only difference between this example and Example 2 is that in step S3, the mixing speed during the addition of hydrophobic silica aerogel is 100 r / min.
[0094] Except for the rotation speed of adding hydrophobic silica aerogel, the types of raw materials, the amount of raw materials, the order of adding materials, the batches of materials, the amount of materials added per batch, the adding time, the mixing speed and the mixing time are all the same as in Example 2.
[0095] Example 5: The only difference between this example and Example 2 is that in step S3, the mixing speed during the addition of hydrophobic silica aerogel is 120 r / min.
[0096] Except for the rotation speed of adding hydrophobic silica aerogel, the types of raw materials, the amount of raw materials, the order of adding materials, the batches of materials, the amount of materials added per batch, the adding time, the mixing speed and the mixing time are all the same as in Example 2.
[0097] Example 6: In this example, the amount of zirconium tungstate is 5.2 parts and the amount of β-lithium nepheline is 2.8 parts, with a total amount of 8 parts.
[0098] Except for the individual amounts of zirconium tungstate and β-lithium nepheline, the types and amounts of other raw materials, the total amount of thermal expansion regulating powder, and the preparation process are the same as in Example 1.
[0099] Example 7: In this example, the amount of zirconium tungstate is 2.8 parts and the amount of β-lithium nepheline is 5.2 parts, with a total amount of 8 parts.
[0100] Except for the individual amounts of zirconium tungstate and β-lithium nepheline, the types and amounts of other raw materials, the total amount of thermal expansion regulating powder, and the preparation process are the same as in Example 1.
[0101] Comparative Example 1: The only difference between this comparative example and Example 2 is that in step S3, the mixing speed during the addition of hydrophobic silica aerogel is 75 r / min.
[0102] Except for the rotation speed of adding hydrophobic silica aerogel, the types of raw materials, the amount of raw materials, the order of adding materials, the batches of materials, the amount of materials added per batch, the adding time, the mixing speed and the mixing time are all the same as in Example 2.
[0103] Comparative Example 2: The only difference between this comparative example and Example 2 is that in step S3, the mixing speed during the addition of hydrophobic silica aerogel is 125 r / min.
[0104] Except for the rotation speed of adding hydrophobic silica aerogel, the types of raw materials, the amount of raw materials, the order of adding materials, the batches of materials, the amount of materials added per batch, the adding time, the mixing speed and the mixing time are all the same as in Example 2.
[0105] Comparative Example 3: This comparative example is based on Example 2, except that 4 parts of zirconium tungstate are removed, while the amount of β-nepheline remains at 4 parts. No other materials are used to make up for the removed zirconium tungstate.
[0106] The raw materials for this comparative example include: The composition includes 30 parts water-based heat-resistant adhesive, 18 parts water, 0.8 parts dispersant, 0.4 parts wetting agent, 0.2 parts primary defoamer, 4 parts β-nepheline, 4 parts rutile titanium dioxide, 2 parts silicon carbide, 6 parts sericite, 3 parts flaky kaolin, 0.6 parts thickener, 12 parts hollow glass microspheres, 4 parts cenospheres, 12 parts hydrophobic silica aerogel, 0.5 parts anti-settling agent, 0.3 parts leveling agent, and 0.2 parts secondary defoamer.
[0107] The preparation method is the same as in Example 2. In step S1, the 4 parts of β-nepheline are divided into 4 batches, with 1 part in each batch, and added to the continuous liquid phase according to the feeding interval, dispersion speed and dispersion time in Example 2.
[0108] Except for the omission of 4 parts of zirconium tungstate, the amounts of other raw materials and the preparation process parameters are the same as in Example 2.
[0109] Comparative Example 4: The raw material composition of this comparative example is exactly the same as that of Example 2, but it is prepared using a common high-speed dispersion process.
[0110] Add 30 parts of water-based heat-resistant adhesive and 18 parts of water to the mixing system and mix at 400 r / min for 5 min; add 0.8 parts of dispersant, 0.4 parts of wetting agent and 0.2 parts of first defoamer and mix at 700 r / min for 10 min.
[0111] Subsequently, 4 parts zirconium tungstate, 4 parts β-lithium nepheline, 4 parts rutile titanium dioxide, 2 parts silicon carbide, 6 parts sericite, 3 parts flaky kaolin, 12 parts hollow glass microspheres, 4 cenospheres, and 12 parts hydrophobic silica aerogel were added sequentially. After all solid raw materials were added, they were dispersed at 1800 r / min for 40 min.
[0112] After dispersion, add 0.6 parts thickener, 0.5 parts anti-settling agent, 0.3 parts leveling agent and 0.2 parts second defoamer, and mix at 600 r / min for 20 min.
[0113] The obtained coating was defoamed for 15 minutes at 25℃ and 35kPa absolute pressure to obtain the control coating.
[0114] This comparative example does not employ the process sequence of first dispersing thermal expansion regulating powder and high-temperature resistant inorganic powder, then adding flaky mineral fillers, adding hollow particles at low speed, and finally adding hydrophobic silica aerogel at low speed.
[0115] Preparation of coated samples A Q235 steel plate with dimensions of 150mm×75mm×2mm was used as the base material. The steel plate was subjected to degreasing, sandblasting and dust removal treatments in sequence, and the surface roughness Ra after treatment was 3.0~6.0μm.
[0116] The coatings prepared in the examples and comparative examples were applied to the surface of steel plates. Each coating was applied in three layers, with each layer having a wet film thickness of 1.0 ± 0.1 mm.
[0117] After each coat of paint is applied, place it in an environment of 23±2℃ and 50%±5% relative humidity for 12 hours before applying the next coat.
[0118] After the final layer of construction is completed, the sample is cured in an environment of 23±2℃ and 50%±5% relative humidity for 7 days, and then treated at 80℃ for 4 hours.
[0119] The dry film thickness of the resulting coating was 2.0 ± 0.2 mm. At least three parallel samples were prepared for each example and comparative example.
[0120] This invention selects four indicators for testing: coating thermal deformation difference, hollow particle integrity rate, crack area ratio after thermal cycling, and thermal conductivity.
[0121] Among them, the coating thermal deformation difference is used to evaluate the overall thermal deformation difference between the coating and the metal substrate; the hollow particle integrity rate is used to evaluate the influence of the preparation process on the hollow particle structure; the crack area ratio after thermal cycling is used to evaluate the degree of crack formation and propagation in the coating during repeated heating and cooling processes; and the thermal conductivity is used to evaluate the thermal insulation performance corresponding to the porous structure retention state.
[0122] 1. Coating thermal deformation difference: The coating to be tested is applied to a flat plate with a peelable layer on its surface to obtain a free coating strip with a length of 100 mm, a width of 10 mm, and a thickness of 1.0 ± 0.1 mm.
[0123] The free-coated strip was placed at 23±2℃ for 24 hours, and its initial length L0 was measured.
[0124] The free-coated strip was kept at 200±2℃ for 30 min, and its length L1 was measured. The linear expansion rate of the coating was calculated according to the following formula: Coating linear expansion rate = (L1 - L0) ÷ L0 × 100%.
[0125] The linear expansion rate of Q235 steel substrate was determined using the same method when the temperature was increased from 23℃ to 200℃.
[0126] The difference in thermal deformation of the coating is calculated according to the following formula: Coating thermal deformation difference = |coating linear expansion rate - Q235 steel substrate linear expansion rate|.
[0127] Three parallel samples were tested in each group, and the arithmetic mean was taken.
[0128] 2. Hollow particle integrity rate: Take the wet coating prepared in the examples or comparative examples, dilute it with water to 5 times its original mass, and mix it at 50 r / min for 2 min.
[0129] The diluted slurry was placed on a glass slide and allowed to dry naturally. Hollow glass microspheres and cenospheres were then observed using a microscopic imaging device.
[0130] Five fields of view were randomly selected for each sample, and at least 100 hollow particles were counted in each field of view.
[0131] Particles with a continuous shell profile and no through cracks, obvious collapses, or large-area gaps are recorded as intact hollow particles.
[0132] The integrity rate of hollow particles is calculated using the following formula: Hollow particle integrity rate = Number of intact hollow particles ÷ Total number of hollow particles counted × 100%.
[0133] 3. Crack area ratio after thermal cycling: The coating sample was heated from 23±2℃ to 250±5℃ at a rate of 5℃ / min, held at 250±5℃ for 60min, then naturally cooled to 80℃, and then cooled to 23±5℃ and held for 30min to complete one thermal cycle.
[0134] Each sample was subjected to 100 consecutive hot and cold cycles.
[0135] After the thermal cycling is completed, images of the coating surface are obtained using a fixed light source, a fixed shooting distance, and a fixed magnification.
[0136] Three analysis areas of 50mm×50mm were selected for each sample, and crack areas with a width of not less than 0.05mm were extracted by image thresholding.
[0137] Crack area ratio is calculated using the following formula: Crack area ratio = Crack projected area ÷ Total area of the analysis region × 100%.
[0138] Three parallel samples were set up for each group, and the results were taken as the arithmetic mean of the nine analytical regions.
[0139] 4. Thermal conductivity: The coatings from the examples and comparative examples were respectively made into coated plates with a size of 300mm×300mm and a thickness of 10±0.5mm.
[0140] The coated panels were cured for 7 days at 23±2℃ and 50%±5% relative humidity, and then dried to constant weight at 60℃.
[0141] The thermal conductivity of the coated panel at an average temperature of 50°C was determined using a steady-state method. Three parallel samples were tested in each group, and the arithmetic mean was taken.
[0142] Table 1. Variables and test results for the examples and comparative examples. Example 1 0.083 91.8 0.74 0.048 Example 2 0.061 92.1 0.42 0.047 Example 3 0.074 91.5 0.58 0.049 Example 4 0.060 94.7 0.31 0.044 Example 5 0.063 89.6 0.66 0.051 Example 6 0.112 91.7 1.86 0.050 Example 7 0.126 91.3 2.24 0.052 Comparative Example 1 0.065 88.2 1.43 0.056 Comparative Example 2 0.064 78.4 3.71 0.066 Comparative Example 3 0.184 91.9 5.28 0.051 Comparative Example 4 0.086 61.7 7.64 0.083 As shown in Table 1, for Examples 1-3 and Examples 6-7, under the conditions that the total amount of thermal expansion regulating powder is 8 parts, and the other raw material types, raw material amounts and preparation processes are the same, the mass ratios of zirconium tungstate to β-nepheline in Examples 1-3 are 1:0.6, 1:1 and about 1:1.67, respectively, and the coating thermal deformation differences are 0.083%, 0.061% and 0.074%, respectively, and the crack area ratios after 100 thermal cycles are 0.74%, 0.42% and 0.58%, respectively. In Examples 6 and 7, the mass ratios of zirconium tungstate to β-nepheline are about 1:0.54 and 1:1.86, respectively, and the coating thermal deformation differences are 0.112% and 0.126%, respectively, and the crack area ratios after 100 thermal cycles are 1.86% and 2.24%, respectively.
[0143] The above results indicate that the relative amounts of zirconium tungstate and β-lithium nepheline affect the thermal deformation matching and thermal cycling stability between the coating and the metal substrate. Specifically, when the mass ratio of zirconium tungstate to β-lithium nepheline is controlled between 1:0.6 and 1:1.7, Examples 1-3 exhibit lower coating thermal deformation differences and lower crack area ratios after thermal cycling. When the relative amount of zirconium tungstate is too low, the compensation effect for the positive thermal expansion of the continuous film-forming phase and other inorganic fillers is insufficient. When the relative amount of zirconium tungstate is further increased and exceeds the above-mentioned preferred ratio range, the overall thermal deformation of the coating may also deviate from the thermal deformation state of the substrate.
[0144] Comparing Examples 2, 4, and 5 with Comparative Examples 1 and 2, it can be seen that when the mixing speed during the addition of hydrophobic silica aerogel is 80 r / min, 100 r / min, and 120 r / min, the hollow particle integrity rate, crack area ratio after thermal cycling, and thermal conductivity are generally better than those of the comparative examples with mixing speeds of 75 r / min and 125 r / min. Specifically, Example 4, at 100 r / min, has a hollow particle integrity rate of 94.7%, a crack area ratio of 0.31% after 100 thermal cycles, and a thermal conductivity of 0.044 W / (m·K).
[0145] The above results indicate that controlling the mixing speed during the addition of hydrophobic silica aerogel to 80–120 r / min is beneficial for both the dispersion of the aerogel and the maintenance of its porous and hollow structures. When the mixing speed is too low, the aerogel is not sufficiently dispersed in the high-viscosity slurry; when the mixing speed is too high, the fluid shear and particle collision effects on the aerogel particles and hollow particles are enhanced, which is detrimental to the maintenance of the porous and hollow structures.
[0146] Comparing Example 2 and Comparative Example 3, it can be seen that in Comparative Example 3, after removing 4 parts of zirconium tungstate and retaining only 4 parts of β-lithium nepheline, the difference in thermal deformation of the coating increased from 0.061% in Example 2 to 0.184%, and the crack area ratio after 100 thermal cycles increased from 0.42% to 5.28%. These results indicate that using β-lithium nepheline alone is insufficient to achieve the same thermal deformation regulation effect as when zirconium tungstate and β-lithium nepheline are used together in Example 2. The combination of these two types of thermal expansion regulating components is beneficial for improving the thermal deformation matching between the coating and the metal substrate.
[0147] Comparing Example 2 and Comparative Example 4, it can be seen that Comparative Example 4, employing a common high-speed dispersion and non-staged feeding process, reduced the hollow particle integrity rate to 61.7%, increased the crack area ratio to 7.64% after 100 thermal cycles, and improved the thermal conductivity to 0.083 W / (m·K). The results indicate that, compared to common high-speed dispersion, the present invention, by implementing staged sequential feeding according to the morphology and shear resistance of different particles and by reducing the mixing speed in stages, helps to reduce damage to hollow particles and the porous structure of the aerogel during the preparation process, thereby maintaining the thermal insulation structure of the coating and improving the structural stability after thermal cycling.
[0148] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A method for preparing a cold and heat cycle resistant aerogel insulating coating for industrial thermal pipelines, characterized in that, Includes the following steps: S1. A water-based heat-resistant binder, water, dispersant, wetting agent, and first defoamer are mixed to obtain a continuous liquid phase; thermal expansion regulating powder and high-temperature resistant inorganic powder are added sequentially to the continuous liquid phase and dispersed to obtain a first slurry; the thermal expansion regulating powder contains one or more of zirconium tungstate, hafnium tungstate, zirconium molybdate, β-lithium nepheline, and cordierite; the high-temperature resistant inorganic powder contains one or more of rutile titanium dioxide, silicon carbide, iron oxide black, and zircon powder. S2. Reduce the mixing speed of the first slurry, add flaky mineral filler to the first slurry, mix, add thickener, and continue mixing to obtain the second slurry; the flaky mineral filler includes one or more of sericite, mica powder, expanded vermiculite, flaky talc, and flaky kaolin. S3. Reduce the mixing speed of the second slurry, add hollow particles to the second slurry in batches, mix, add hydrophobic silica aerogel, and continue mixing to obtain the third slurry; the hollow particles include one or more of hollow glass microspheres, hollow ceramic microspheres, and cenospheres; S4. Add anti-settling agent, leveling agent and second defoamer to the third slurry, mix and adjust to the target viscosity with water, and defoam to obtain the cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines; wherein, the dispersion speed in step S1 is greater than the mixing speed in step S2, and the mixing speed in step S2 is greater than the mixing speed after adding hydrophobic silica aerogel in step S3.
2. The preparation method of the cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines according to claim 1, characterized in that, The preparation of the continuous liquid phase in step S1 includes: Mix 20-40 parts by weight of water-based heat-resistant adhesive, 8-25 parts by weight of water, 0.2-1.5 parts by weight of dispersant, 0.1-0.8 parts by weight of wetting agent and 0.05-0.5 parts by weight of first defoamer; The waterborne heat-resistant adhesive comprises one or more of waterborne organosilicon resin, waterborne silicone-acrylic emulsion, waterborne siloxane resin, waterborne silicate adhesive, and waterborne organic-inorganic hybrid resin, wherein the solid content of the waterborne heat-resistant adhesive is 35% to 65%. The dispersant comprises one or more of polycarboxylate dispersants, polyacrylate dispersants, polyphosphate dispersants, and nonionic polymeric dispersants. The wetting agent comprises one or more of polyether-modified siloxane wetting agents, acetylsalicylic acid diol wetting agents, and nonionic polyether wetting agents. The mixing speed of the continuous liquid phase is 300-900 r / min, the mixing time is 5-20 min, and the mixing temperature is 15-40℃.
3. The preparation method of the cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines according to claim 1, characterized in that, The addition and dispersion of the thermal expansion regulating powder in step S1 includes: Add 4 to 20 parts of the thermal expansion regulating powder to the continuous liquid phase according to the mass fraction; The thermal expansion regulating powder contains at least one of zirconium tungstate, hafnium tungstate, and zirconium molybdate, and at least one of β-nepheline and cordierite; The ratio of the total mass of zirconium tungstate, hafnium tungstate, and zirconium molybdate to the total mass of β-lithium nepheline and cordierite is 1:0.3 to 1:
4. The D50 of the zirconium tungstate, hafnium tungstate, and zirconium molybdate is 0.2–8 μm, and the D50 of the β-lithium nepheline and cordierite is 1–20 μm. The thermal expansion regulating powder is added in 2 to 5 batches, with a time interval of 1 to 8 minutes between adjacent batches. After each batch is added, it is dispersed at 900 to 2200 r / min for 3 to 12 minutes. After all the powder is added, it is dispersed at 1000 to 2500 r / min for 10 to 35 minutes.
4. The preparation method of the cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines according to claim 1, characterized in that, The addition and dispersion of the high-temperature resistant inorganic powder in step S1 includes: According to the mass fraction, add 2 to 15 parts of the high-temperature resistant inorganic powder to the continuous liquid phase after adding the thermal expansion regulating powder; The high-temperature resistant inorganic powder includes a first inorganic powder and a second inorganic powder. The first inorganic powder contains at least one of rutile titanium dioxide and zircon powder, and the second inorganic powder contains at least one of silicon carbide and iron oxide black. The mass ratio of the first inorganic powder to the second inorganic powder is 1:0.1 to 1:2; The rutile titanium dioxide has a D50 of 0.1–1.5 μm, and the silicon carbide, iron oxide black, and zircon powder have D50s of 0.5–15 μm, respectively. The high-temperature resistant inorganic powder is added at a feeding rate of 0.2 to 2.0 kg / min, and the dispersion speed during the feeding process is 1000 to 2500 r / min. After the feeding is completed, the dispersion continues for 10 to 40 min to obtain a first slurry with a fineness of 20 to 80 μm.
5. The preparation method of the cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines according to claim 1, characterized in that, The addition and mixing of the flaky mineral filler in step S2 includes: According to the mass fraction, add 4 to 18 parts of the flaky mineral filler to the first slurry; The flaky mineral filler comprises sericite or mica powder, and contains at least one of expanded vermiculite, flaky talc, and flaky kaolin. The ratio of the total mass of the sericite and mica powder to the total mass of the expanded vermiculite, flaky talc, and flaky kaolin is 1:0.2 to 1:
3. The D50 of the sheet-like mineral filler is 10-100 μm, and the aspect ratio is 10:1-80:
1. The flaky mineral filler is added in 3 to 6 batches, with each batch containing 10% to 40% of the total mass of the flaky mineral filler. The mixing speed during the feeding process is 300 to 800 r / min, and each batch is mixed for 3 to 10 minutes after addition. After all the flaky mineral filler is added, 0.1 to 1.5 parts by weight of thickener is added, and the mixture is stirred at 200 to 700 r / min for 10 to 30 min to obtain the second slurry.
6. The preparation method of the cold and heat cycle resistant aerogel thermal insulation coating for industrial thermal pipelines according to claim 1, characterized in that, The addition and mixing of hollow particles in step S3 includes: Add 8 to 28 parts of the hollow particles to the second slurry according to the mass fraction; The hollow particles comprise at least one of hollow glass microspheres and hollow ceramic microspheres, and also include cenospheres; The ratio of the total mass of the hollow glass microspheres and hollow ceramic microspheres to the mass of the cenospheres is 1:0.1 to 1:2; The hollow glass microspheres have a particle size of 15–120 μm, the hollow ceramic microspheres have a particle size of 20–150 μm, and the cenospheres have a particle size of 30–180 μm. The bulk density of the hollow particles is 0.08–0.65 g / cm³. 3 ; The hollow particles are added in 4 to 8 batches, with each batch accounting for 8% to 30% of the total mass of the hollow particles. The mixing speed during the feeding process is 100 to 500 r / min. After each batch is added, the mixture is mixed for 2 to 8 minutes. After all the hollow particles have been added, the mixture continues to be mixed for 5 to 20 minutes.
7. The preparation method of the cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines according to claim 1, characterized in that, The addition and mixing of hydrophobic silica aerogel in step S3 includes: Add 5 to 22 parts by weight of hydrophobic silica aerogel; The hydrophobic silica aerogel is one or both of granular hydrophobic silica aerogel and powdered hydrophobic silica aerogel. The hydrophobic silica aerogel has a particle size of 5–100 μm and a bulk density of 0.03–0.20 g / cm³. 3 The pore size is 10–100 nm; The surface of the hydrophobic silica aerogel contains one or more of trimethylsiloxy, dimethylsiloxy and methylsiloxy groups; Before adding the hydrophobic silica aerogel, the mixing speed in step S3 is adjusted to 50-250 r / min; The hydrophobic silica aerogel is added continuously at a feeding rate of 0.05–0.8 kg / min or in 2–6 batches. After the feeding is completed, it is mixed at 80–250 r / min for 5–20 min at a mixing temperature of 15–35 °C to obtain the third slurry.
8. The preparation method of the cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines according to claim 1, characterized in that, Step S4 includes: According to the mass fractions, add 0.1 to 1.5 parts of anti-settling agent, 0.05 to 0.8 parts of leveling agent and 0.05 to 0.6 parts of second defoamer to the third slurry; The anti-settling agent comprises one or more of water-based bentonite, modified attapulgite, polyamide wax, and fumed silica. The leveling agent comprises one or both of polyether-modified siloxane leveling agents and polyacrylate leveling agents; The mass ratio of the first defoamer to the second defoamer is 1:0.3 to 1:3; After adding the anti-settling agent, leveling agent, and second defoamer, mix at 100–500 r / min for 8–30 min, and add 0.5–8 parts by weight of water to adjust the viscosity of the coating at 25°C to 5 × 10⁻⁶. 3 ~4×10 4 mPa·s; After viscosity adjustment, degas for 5–30 minutes at 15–40℃ and 10–70 kPa absolute pressure.
9. The preparation method of the cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines according to claim 1, characterized in that, Step S3 employs a segmented speed-reduction mixing method, including: Before adding the hollow particles, the second slurry is mixed at 300-600 r / min for 2-8 min; During the addition of the hollow particles, the mixing speed is adjusted to 150–450 r / min; After the hollow particles are added, adjust the mixing speed to 100-350 r / min and mix for 5-15 min. Before adding the hydrophobic silica aerogel, the mixing speed is adjusted to 50-200 r / min; During the addition of the hydrophobic silica aerogel, the mixing speed is maintained at 80–120 r / min; After the hydrophobic silica aerogel is added, the mixing speed is adjusted to 80-250 r / min, and the mixture is mixed for 5-20 min. The total mixing time for step S3 is 20–70 min.
10. A cold and heat cycle resistant aerogel insulation coating for industrial thermal pipelines, characterized in that, By weight, it includes: 20-40 parts of water-based heat-resistant adhesive; Water 8.5–33 parts; Dispersant 0.2–1.5 parts; Wetting agent 0.1 to 0.8 parts; Defoamer 0.1 to 1.1 parts; 4-20 parts of thermal expansion regulating powder; 2-15 parts of high-temperature resistant inorganic powder; 4-18 parts of flaky mineral filler; Thickener 0.1 to 1.5 parts; Hollow granules, 8-28 parts; 5–22 parts of hydrophobic silica aerogel; Anti-settling agent 0.1–1.5 parts; Leveling agent 0.05–0.8 parts; The thermal expansion regulating powder contains at least one of zirconium tungstate, hafnium tungstate, and zirconium molybdate, and at least one of β-nepheline and cordierite; The high-temperature resistant inorganic powder includes a first inorganic powder and a second inorganic powder. The first inorganic powder contains at least one of rutile titanium dioxide and zircon powder, and the second inorganic powder contains at least one of silicon carbide and iron oxide black. The flaky mineral filler comprises sericite or mica powder, and contains at least one of expanded vermiculite, flaky talc, and flaky kaolin. The hollow particles comprise at least one of hollow glass microspheres and hollow ceramic microspheres, and also include cenospheres; The hydrophobic silica aerogel has a particle size of 5–100 μm, the hollow particles have a particle size of 15–180 μm, and the sheet-like mineral filler has a D50 of 10–100 μm and a diameter-to-thickness ratio of 10:1–80:1.